2016
DOI: 10.3847/0004-637x/830/2/71
|View full text |Cite
|
Sign up to set email alerts
|

Silicate Composition of the Interstellar Medium

Abstract: The composition of silicate dust in the diffuse interstellar medium and in protoplanetary disks around young stars informs our understanding of the processing and evolution of the dust grains leading up to planet formation. Analysis of the well-known 9.7µm feature indicates that small amorphous silicate grains represent a significant fraction of interstellar dust and are also major components of protoplanetary disks. However, this feature is typically modelled assuming amorphous silicate dust of olivine and py… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 66 publications
1
39
1
Order By: Relevance
“…Interstellar grains are composed by two types of refractory material (Hoyle & Wickramasinghe 1969; Jones et al 2013): carbonaceous grains, which include graphite, amorphous carbon, hydrogenated amorphous carbon and silicon carbide (Duley 1988; Witt & Schild 1988; Amari et al 1990; Duley 1994; Furton et al 1999; Draine & Li 2007), and silicates, which can mainly be found in an amorphous state although crystalline phases have also been detected (Witt et al 1998; Furton et al 1999; Li & Draine 2001; Bowey et al 2004; Li et al 2007; Henning 2010; Fogerty et al 2016). Among the most astrophysical relevant silicates, olivines (with general formula Mg 2 x Fe (2 x −2) SiO 4 ) have been thoroughly studied and positively identified by infrared spectroscopy (Henning 2010) and by identification of refractory material carried by the Stardust mission (Zolensky et al 2006).…”
Section: Water Formation On Grain Surfaces: Previous Studiesmentioning
confidence: 99%
“…Interstellar grains are composed by two types of refractory material (Hoyle & Wickramasinghe 1969; Jones et al 2013): carbonaceous grains, which include graphite, amorphous carbon, hydrogenated amorphous carbon and silicon carbide (Duley 1988; Witt & Schild 1988; Amari et al 1990; Duley 1994; Furton et al 1999; Draine & Li 2007), and silicates, which can mainly be found in an amorphous state although crystalline phases have also been detected (Witt et al 1998; Furton et al 1999; Li & Draine 2001; Bowey et al 2004; Li et al 2007; Henning 2010; Fogerty et al 2016). Among the most astrophysical relevant silicates, olivines (with general formula Mg 2 x Fe (2 x −2) SiO 4 ) have been thoroughly studied and positively identified by infrared spectroscopy (Henning 2010) and by identification of refractory material carried by the Stardust mission (Zolensky et al 2006).…”
Section: Water Formation On Grain Surfaces: Previous Studiesmentioning
confidence: 99%
“…Because of this, Cyg OB2 No. 12 (an O star with a nominal 2MASS KS-band magnitude of ∼ 2.70 mag) and ζ Ophiuchi (a B star with a nominal KS magnitude of ∼ 2.62 mag), which were used to trace the interstellar silicate extinction in Fogerty et al (2016), are not included in our sample since they are much brighter than the saturation limit of ∼ 5 mag in KS.…”
Section: The Samplementioning
confidence: 99%
“…Also, to account for the free-free emission from the stellar wind of the B5 hypergiant Cyg OB2 No. 12,Fogerty et al (2016) added an λ −0.6 component in the IR spectrum. c 2018 RAS, MNRAS 000, 1-11…”
mentioning
confidence: 99%
“…Olivine (Mg,Fe) 2 SiO 4 is a mineral of prominent importance since it is a major component of the diffuse interstellar medium and of protoplanetary disks around young stars [1]. Olivine dust in the interstellar medium appears to be almost entirely amorphous, whereas the spectra of protoplanetary disks also show evidence of crystallinity.…”
Section: Introductionmentioning
confidence: 99%